The Role of PPKn Teachers in Developing Civic Disposition of Grade VII Students Through the Pancasila Student Profile Strengthening Project (P5) in the OSIS Democracy Voice Activity at SMP Negeri 1 Mataram - Fitri, Raudatul; Zubair, Muh.; Hudori, Ahmad; Kurniawansyah, Edy (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This study aims to describe the role of PPKn teachers in developing civic disposition of grade VII students through the Pancasila student profile strengthening project (P5) in the OSIS democratic voice activity at SMP Negeri 1 Mataram. This study uses a qualitative approach with a case study research type with data collection techniques through documentation, observation, interviews. The data analysis technique used is the data analysis technique according to Milles and Huberman which consists of three stages, namely data reduction, data display, and drawing conclusions. The results of this study are that PPKn teachers have an important role in shaping student character in accordance with Pancasila values. The role of PPKn teachers is as a facilitator, project supervisor, evaluator. The supporting and inhibiting factors experienced by PPKn teachers are supporting factors, namely facilities and infrastructure and P5 guidebooks, while inhibiting factors are time and funding.Â The implementation of the Pancasila student profile strengthening project (P5) through the OSIS democratic voice activity was carried out well and ran according to the guidelines used, namely the module in accordance with the project guidebook. Â 